PERAN MASYARAKAT DALAM PELESTARIAN TERUMBU KARANG DAN DAMPAKNYA TERHADAP PENINGKATAN KESEJAHTERAAN - NFN Widayatun (Research Centre for Population, Indonesian Institute of Sciences, 2011)
As an Archipelago, Indonesia consists of more than 18.000 islands, locating at the heart of the World 'Coral Triangle'. This country is well known as the highest coral reef biodiversity, especially in Raja Ampat, Selayar, Banda and Bunaken. This potential resource, however, in some places has been destroyed, due to oveifishing and destructive fishing practices. The Indonesian government, to address these threats has developed Coral Reefs Rehabilitation and Management Program or Coremap since the 2006. Coremap aims to manage, rehabilitate and protect coral reefs to ensure sustainable utilization of these marine resources for reducing poverty of coastal community and increasing their welfare. Coremap focuses on collaborative management by involving communities, locaand national governments, NGOs and other relevant stakeholders. This paper is based on data from the 2008 and 2011 studies on socio-economic aspects of coral reefs in Coremap locations in the eastern part of Indonesia. The studies applied a combination between quantitative (survey) and qualitative (indepth interview and focus group discussions) approaches. The study results informed that community has quite high participation in the management and their welfare also tends to increase during this periodKeywords: coral reefs rehabilitation, community participation and roles, welfare",